Pengaruh Pengendalian Internal Sistem Pemberian Kredit, Kemampuan Mengelola Kredit, Dan Karakter Nasabah Terhadap Kredit Macet - Ni Wayan Diah Sri Parwati; Ni Wayan Alit Erlina Wati (UNHI Press, 2022)
The importance of keeping the cooperative from a bad credit situation becomes an important task and responsibility. This research is specifically made to see things that can be done to overcome bad credit through factors. This research is located in Internal Control of Credit Provision, Credit Management Ability, and Customer Character Against Bad Loans. This research was conducted at the Savings and Loans Cooperative (KSP) in Tabanan District, where all employees were made into a population of 608 people. 160 of them were selected for the sample by determining the sample using purposive sampling technique and tested using multiple linear regression analysis technique. This study found that bad loans in cooperatives could be avoided by looking at the company's internal control factors, the ability of customers to manage credit, and the characteristics of the customers themselves.